2019 IEEE International Symposium on Software Reliability Engineering Workshops (ISSREW) 2019
DOI: 10.1109/issrew.2019.00053
|View full text |Cite
|
Sign up to set email alerts
|

Simulation-Based Testing to Improve Safety of Autonomous Robots

Abstract: Autonomous systems are becoming increasingly popular among industries as well as end-users, and are deployed in numerous tasks. To improve their reliability and to avoid critical failures that impact safety, their testing aims at ensuring that their behavior and decisions are acceptable even in scenarios that have not been foreseen by the developers. As testing of these systems is usually done through field testing, which is costly and is limited in the reproducible scenarios, system-level pre-validation can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Authors Ejdys and Halicka also stated that the implementation of new technologies depends on cultural factor like trust in technology (Ejdys and Halicka, 2018). Autonomous robots need to be tested and their decisions studied in different scenarios to ensure safety for humans (Sartori, 2019). According to the latest research, robots were shown to have benevolent stated social intentions (Lyons et al, 2022).…”
Section: Examples Of Innovative Ict To Support E-commerce Processes I...mentioning
confidence: 99%
“…Authors Ejdys and Halicka also stated that the implementation of new technologies depends on cultural factor like trust in technology (Ejdys and Halicka, 2018). Autonomous robots need to be tested and their decisions studied in different scenarios to ensure safety for humans (Sartori, 2019). According to the latest research, robots were shown to have benevolent stated social intentions (Lyons et al, 2022).…”
Section: Examples Of Innovative Ict To Support E-commerce Processes I...mentioning
confidence: 99%